2020
DOI: 10.3390/ma13051155
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Activation of Copper and Nickel Slag Composite Cementitious Materials

Abstract: Alkali-activated copper and nickel slag cementitious materials (ACNCMs) are composite cementitious materials with CNS (copper and nickel slag) as the main materials and GGBFS (ground-granulated blast-furnace slag) as a mineral admixture. In this paper, the activity indexes of CNS with different grinding times were studied using CNS to replace a portion of cement. NaOH, Na2SO4, and Na2SiO3 activators were used to study the alkaline solution of the CNS glass phase. The effects of the fineness of CNS and the type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Numerous investigations have found that the precursor composition in AAMs [58][59][60][61][62][63][64] has an obvious influence on the resistance to carbonation. This is mainly attributed to differences in the content of calcium, silicon, magnesium, and aluminum in the precursors and, thus, variations in the hydration products.…”
Section: Type Of Precursorsmentioning
confidence: 99%
“…Numerous investigations have found that the precursor composition in AAMs [58][59][60][61][62][63][64] has an obvious influence on the resistance to carbonation. This is mainly attributed to differences in the content of calcium, silicon, magnesium, and aluminum in the precursors and, thus, variations in the hydration products.…”
Section: Type Of Precursorsmentioning
confidence: 99%
“…In recent years, the research on alkali-activated cementitious materials mainly focuses on two directions. First, continue to study alkali-activated slag cementitious materials to improve their properties and expand their applications [ 21 , 22 , 23 ]; Second, other solid wastes with alkali-activated cementitious properties are used to prepare new alkali-activated cementitious materials, such as silicomanganese slag, copper and nickel slag, red mud-iron tailings, copper slag, nickel slag, and ferronickel slag [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mussapyrova, et al (2021) [ 11 ] used mechanical activation on GCS. Zhang, et al (2020) [ 12 ] investigated the properties of alkali-activated GCS cementitious materials using sodium hydroxide (NaOH) and sodium sulphate (Na 2 SO 4 ) solutions. These methods usually induce intensive energy consumption and were not very effective.…”
Section: Introductionmentioning
confidence: 99%